Pengembangan Canti sebagai Desa Wisata Pesisir Tangguh Bencana Berbasis pada Kearifan Lokal - Melvi, Melvi; Muda, Mona Arif; Akbar, Yusuf Rizki Sulardi; Wahidy, Yusril; Ulvan, Ardian (Jurnal Nusantara Mengabdi, 2024)
Purpose: This initiative aims to transform Canti Village into a disaster-resilient coastal tourism destination by leveraging its unique local wisdom, culture, and natural resources. The objective was to empower the community, revitalize local businesses, and position Canti Village as a thriving tourism hub. Methodology: The initiative employed a participatory approach, engaging the village government, local stakeholders, and community members through workshops, focus-group discussions, and hands-on training. Key activities included assessing the village’s natural, maritime, and historical attractions; identifying dormant businesses; and providing capacity-building sessions on entrepreneurship, disaster resilience, and technology integration. Results: The initiative achieved significant milestones, including the revitalization of dormant businesses, enhancement of community knowledge on disaster resilience, and introduction of technology to existing entrepreneurs. The program also helped to position Canti Village as a potential tourism hub by developing value-added products and services. Furthermore, community members exhibited an increased readiness to serve as tourism actors, demonstrating a commitment to promoting the village’s cultural and natural heritage. Limitations: The primary challenges include limited financial resources and the need for ongoing technical support to sustain the initiative's outcomes. Additionally, infrastructural constraints and the limited digital literacy of some community members pose hurdles in achieving broader technological integration. Contributions: This initiative contributes to regional development by fostering disaster-resilient and sustainable tourism. It also serves as a model for integrating local wisdom into tourism development, promoting cultural preservation, and enhancing economic opportunities in rural communities.